Correlation of plasmatic sodium determined by the laboratory and that determined by the dialysis machine - Casals, Joaquim; Broseta, José Jesús; Fernández, Rosa María; Rodriguez-Espinosa, Diana; del Risco, Jimena; Gómez, Miquel; Rodas, Lida M.; Arias-Guillén, Marta; Vera, Manel; Fontseré, Néstor; Rico, Naira; Maduell, Francisco (Nefrología, 2024)
Changes in plasma sodium concentration (pNa, expressed in mEq/L) are common in hemodialysis (HD) patients. Hemodialysis monitors can estimate pNa by using an internal algorithm based on ion dialysance measurements. The present study studies the accuracy of the correlation between the pNa estimated by the dialysis monitor and that measured by the biochemistry laboratory at our center. A single-centre prospective observational study in patients on a chronic HD program with the 6008 CAREsystem monitor and standard sodium (138mmol/L) and bicarbonate (32mmol/L) prescriptions. Venous blood samples were drawn from each patient before and after each HD session to ensure inter- and intra-individual validity. The pNa was measured in the biochemistry laboratory using indirect potentiometry and simultaneously the estimated pNa by the HD monitor was recorded at the beginning and at the end of the HD session. For statistical analysis, a scatterplot was made, and Spearman’s correlation quotient was calculated. In addition, the differences between both methods were represented as Bland-Altman diagrams. The pre-dialysis pNa measured in the laboratory was 137.49±3.3, and that of the monitor, 137.96±2.91, with a correlation with R2 value of 0.683 (p<0.001). The post-dialysis pNa measured in the laboratory was 137.08±2.23, and that of the monitor was 138.87±1.88, with an R2 of 0.442 (p<0.001). On the Bland-Altman plots, the pre-dialysis pNa has a systematic error of 0.49, in favor of the monitor-estimated pNa, with a 95% confidence interval (CI) of (−3.24 to a 4.22). In the post-dialysis pNa, a systematic error of 1.79 with a 95% CI of (−1.64 to 5.22) was obtained. The correlation between the pNa estimated by Fresnius 6008 CAREsystem HD monitor and that measured by the laboratory is good, especially pre-dialysis measurements. Further studies should verify the external validity of these results. Las alteraciones de la concentración plasmática de sodio (Nap, expresado en mEq/L) son frecuentes en pacientes en hemodiálisis (HD). Los monitores de hemodiálisis tienen la capacidad de estimar la Nap mediante un algoritmo interno a partir de las medidas de la dialisancia iónica. En el presente estudio se estuda la correlacionación entre la Nap estimada por el monitor de diálisis y la medida enel laboratorio de bioquímica de nuestro centro. Estudio observacional prospectivo y unicéntrico en pacientes en programa crónico de HD con el monitor 6008 CAREsystem y prescripción estándar de sodio (138 mEq/L) y bicarbonato (32mmol/L). De cada paciente se extrajeron muestras de sangre venosa antes y después de la sesión para asegurar validez inter e intraindividual. Se analizó la Nap en el laboratorio mediante potenciometría indirecta y simultáneamente se registraba la estimada por el monitor de HD al inicio y al terminar la sesión. Para el análisis estadístico se realizó un diagrama de dispersión y se calculó el cociente de correlación de Spearman. Además, se representaron las diferencias entre métodos mediante diagramas de Bland-Altman. La Nap prediálisis medida en el laboratorio fue de 137,49±3,3, y el del monitor 137,96±2,91, con una correlación con valor de R2 de 0,683 (p<0,001). La Nap postdiálisis medida en el laboratorio fue de 137,08±2,23 y la del monitor de 138,87±1,88, con una R2 de 0,442 (p<0,001). En los diagramas de Bland-Altman, la Nap prediálisis obtuvo un error sistemático de 0,49 mEq/L a favor de la Nap estimada por el monitor, con un intervalo de confianza (IC) al 95% de (−3,24–4,22). En cuanto a la Nap postdiálisis, se obtuvo un error sistemático de 1,79 mEq/L con un IC al 95% de (−1,64–5,22). La correlación entre la Nap estimada por el monitor de HD 6008 CAREsystem de Fresenius y la medida por el laboratorio es buena, siendo mejor en las mediciones prediálisis. Nuevos estudios deberán comprobar la validez externa de estos resultados.